Asesmen Penilaian di RA Al-Ashriyah Kota Langsa Pada Saat Pandemi Covid-19 - Mawaddah Ulya; Siti Fatonah (Jurnal Pendidikan Raudhatul Athfal, 2021)
In the teaching and learning process to achieve developmental aspects in early childhood, an assessment is needed which is useful for assessing the development, ability level, performance and skills of the child. This paper is the result of observations made by the author at RA Al-Ashriyah in the Covid-19 era, who in his observations identified the assessments used by teachers in the learning process online. Data collection was carried out by researchers through interviews and documentation. The first data collection, namely interviews conducted by the principal RA Al-Ashriyah in order to collect information related to learning and assessment used by teachers in the Covid-19 era and the second collection of data used, namely documentation, documentation collected in the form of research supporting files as supporting data Interview result.